Radio Propagation Prediction Using SBR in a Tunnel with Narrow Cross-Section and Obstacles - Gunduzalp, Emrullah; Yildirim, Gungor; Tatar, Yetkin (Ieee, 2019)
Ray tracing (RT) techniques are successful deterministic approaches used in predicting radio propagations. One of the best known RT techniques is Shooting and Bouncing Rays (SBR). SBR can give effective results in especially indoor environments containing obstacles. In this study, a radio propagation prediction in a tunnel with narrow cross-section and obstacles is carried out using SBR. In the SBR technique used, Snell's law and Keller's Cone are used for the geometrical calculations. The electromagnetic loss calculations are carried out with the help of Fresnel's law and UTD (Uniform Theory of Diffraction). The SBR technique is used in a revised 3D simulator environment, called RayLA developed in Java and JOGL. In the study, the signal levels from a source running at 2.4 GHz have been first measured in a real tunnel with narrow-section and obstacles, and the tunnel environment has been modeled in the 3D simulator. Then, the results obtained from the SBR technique have been compared with both the real measurements and the results taken from OMNET++/Castalia which is another simulation platform.
3rd International Conference on Applied Automation and Industrial Diagnostics (ICAAID) -- SEP 25-27, 2019 -- Elazig, TURKEY
Keywords: 3D Ray Tracing; Shoot and Bouncing Rays; RF Propagation; Keller Cone; UTD